Association of adenylate cyclase activity in vasopressor-type neurally mediated syncope based on the α2b-AR gene - Tomoyoshi Komiyama; Kengo Ayabe; Kunzo Orita; Ayumi Sasaki; Yuka Kitamura; Hideyuki Matsuzawa; Teppei Yamashita; Eiichiro Nagata; Yasuhiro Kanatani; Koichiro Yoshioka (PLoS ONE, 2025)
Neurally mediated syncope (NMS) arises from a neural reflex; however, its underlying cause remains unknown. Previous research has shown that variations in the Gi-α signal transduction rate led to changes in adenylate cyclase (AC) activity levels. Thus, we hypothesized that these fluctuations in AC activity could contribute to NMS. This study aimed to investigate the receptor genes associated with glutamate (Glu) repeat polymorphism sites Glu12 and Glu9 in the α2B-AR gene. A total of 50 patients with vasodepressor-type (VT)-NMS and 20 healthy volunteers were included in this study. We assessed AC activity levels and blood pressure responses during the head-up tilt (HUT) test and conducted a Glu repeat polymorphism analysis to explore its potential association with NMS. Our findings showed significantly higher AC activity in patients with the Glu12/12 homotype than healthy volunteers across all four HUT test points. Conversely, patients with the Glu9/12 heterotype exhibited a significant difference only 10 min after the test initiation, suggesting a pronounced activation effect of the β2-AR Gs-α subunit in these individuals. Both genotypes displayed the greatest blood pressure fluctuations under 70° tilt stress, with patients with Glu12/12 showing consistent cardiac load and higher values than those with Glu9/12 at two points. Notably, the frequency of NMS onset within 20 min during the tilt test varied, with one Glu12/12 patient and seven Glu9/12 patients experiencing syncope. Additionally, patients with the Glu9/12 heterotype were found to have a higher risk of syncope after prolonged standing compared to those with the Glu12/12 homotype. These results suggest that patients with the Glu12/12 homotype exhibit elevated AC activity levels, which may help increase blood pressure to prevent syncope. This study underscores that variations in AC activity among different gene types could influence the frequency of NMS onset during standing.